Pengaruh Kualitas Produk, Harga, dan Online Customer Rating Terhadap Keputusan Pembelian Pada Produk UMKM Basreng Sultan Bandung - Oktaviana, Puji Miranti; Sarah, Siti; Wijaya, Fanji (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This technological advancement is very helpful and certainly increases knowledge and makes everything easier, including work. The shift in lifestyle from offline to online has been felt since the COVID-19 pandemic; since 2020, many businesses have utilized this marketplace and social media. The existence of the internet facilitates us in various activities, one of which is online shopping; people can use the marketplace to shop anytime and anywhere. After people recognized the online transaction system, the level of use of online buying and selling services increased. This makes the business segment through the marketplace, which includes Shopee is now increasing. Shopee E-Commerce is an e-commerce that sells various kinds of products. The products available in e-commerce include fashion products, skincare products, shoes, and food products. One of the snack products that many people like nowadays is food made from fried meatballs or basreng. Basreng is a dry-fried meatball snack or snack, a crunchy snack that generally has a spicy taste and is liked by many people from various groups. One of the products the author will examine is the Basreng Sultan Bandung product, founded in 2021. This study aims to determine the effect of product quality, price, and online customer rating on purchasing decisions on basreng sultan Bandung products. This type of research is descriptive quantitative. The sampling technique used non probability sampling with purposive sampling. The population in this study were all followers of the shopee basreng sultan bandung account with 100 respondents. The data collection technique used a questionnaire with a Likert scale. Data u sing validity test, reliability test, classical assumption test, and multiple regression. Results of data analysis show that product quality has a positive partial effect on purchasing decisions, price shows that it has no significant effect on purchasing decisions, and online customer ratings have a partial effect on purchasing decisions. The results of this study will be different from previous research